The Liquidity Premium of Digital Payment Vehicle - Zefeng Chen; Zhengyang Jiang (Center for Economic Studies and ifo Institute (CESifo), 2022)
Do digital payment technologies generate liquidity premia like cash and Treasury? We provide an estimate in the context of the world's largest digital payment platform, Alipay. Our empirical strategy exploits the variation in the timing of the introduction of money market funds that users on this platform can hold and use for digital transactions. We find that, once a fund becomes eligible for these transactions, its size increases by 45 times on average. Through the lens of an equilibrium demand system that models funds as imperfect substitutes, this size increase maps to a liquidity premium of about 0.8% per annum.
Keywords: E41; G12; 330; digital payment; liquidity premium; money market fund